KONTRIBUSI MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN GAMBAR TEKNIK KELAS X TEKNIK GAMBAR BANGUNAN SMK N 2 SOLOK - 2146-2150, Newida N.F Sinambela (Universitas Negeri Padang, 2018)
Abstract—The aim of this research is determine the contribution study motivation of students learning outcomes on tecnique drawing class student for grade X at SMK N 2 Solok. The type of this research is a quantitative research with correlational approach. Samples were taken by using Total sampling formula with number of samples 40 students. The types of data are primary data taken by spread questionnaire and secondary data is students learning outcomes. Result of this research analysis that value of r 0,331 with interpretation coefficient is low, while result of contribution equal to 11,6%. Based of acquire of examination result, can be pull by motivation have contribution to learning outcomes on tecnique drawing class of X Tecnique Drawing at SMK N 2 Solok equal to11,6% .Keywords:Contribution, study motivation, learning achievement